PERSEPSI PESERTA DIDIK TENTANG PENANGANAN DISIPLIN OLEH PERSONIL SEKOLAH DI SMK N 3 PADANG - Opela, Seiber - (Bimbingan dan Konseling, 2014)
This research was background by the condition which was found in field that discipline hasnât run well, because thereâs still student who donât obligate to the school role, teacher tag with other school personal hasnât run well, discipline which is implemented hasnât been done well at school, student recognizing to do it willingly still lack of hope, discipline disobey which is done hasnât been given suit solving. The purpose of it is to describe student perception about discipline solving by teacher and student perception about discipline solving by counselor.This research is descriptive quantitative research. The research population the all of students in SMKN 3 Padang , 430 students. The technique which is used in sampling taking was Simple random sampling, with 60 students who is at class X and XI. The instrument which was used in this research was questionnaire, meanwhile to analyze the data was used criterium formula Sturgess and percentage.The result shown that student in general it has been categorized as good with all teachers and counselor. Based on the result researcher suggested to the school personil and counselor to implement the discipline solving well.